How Transfer Policies Affect Civil Servant Performance: A Systematic Literature Review - Muhimatul Khoiroh; Pantius Drahen Soeling (Eduvest - Journal of Universal Studies, 2025)
This systematic literature review examines the relationship between civil servant transfer policies, including job rotation and mutation, and employee performance in public sector. While such policies aim to enhance workforce flexibility, skill diversification, and career development, they may also cause job dissatisfaction, decreased motivation, and knowledge loss if poorly implemented. To assess the impact of structured and unstructured transfer systems on civil servant performance, a comprehensive analysis of 30 peer-reviewed studies from 2015 to 2025 was conducted using the PRISMA framework. The findings indicate that merit-based and well-planned job rotations generally improve employee adaptability, engagement, and productivity. Conversely, politically influenced or arbitrary transfers often lead to inefficiencies, demotivation, and organizational instability. The review underscores the pivotal function of knowledge management and transparent policies in mitigating the adverse impacts of transfers and ensuring institutional continuity. The review also identifies key research gaps, including the need for longitudinal studies on performance outcomes, the psychological effects of job rotation, and comparative analyses across different public sector institutions. These insights underscore the necessity of formulating evidence-based, equitable, and strategically devised transfer policies that achieve a balance between institutional requirements and employee well-being. Future research endeavors should prioritize the optimizations of transfer frameworks to enhance performance, ensure the retention of knowledge, and cultivate sustainable public sector governance.